Modificação de filtros de ar condicionado com nanopartículas de cobre com efeito biocida para ambientes indoor rooms - Machry, Karine (2020)
Filter media, as used in air conditioning system, are the first physic barrier between external environment and indoor rooms. To avoid the contamination in indoor rooms, one preventive measure is to contain the proliferation of pathogen microorganisms in filter media. The aim of this work was to do a physical characterization of a polyester commercial filter media, in order to visualize the visual aspect of the fibers and quantify the permeability. Present work aimed to synthesize copper nanoparticles, characterize it and impregnated it to filter media, aiming confer biocidal effect. The copper nanoparticles were synthesized by a redox reactionby two methods: using PVP as the dispersant agent and other one using starch. CuNPs were analyzed in XRD as it chemical composition, and in SEM coupled to EDS system to characterize it physically and chemically, respectively. In the end, the impregnation of the nanoparticles to the polyester fiber was done, one only with CuNP and another one with a pretreatment with HCl. Biological analysis with E. coli and S. aureus was done through the contact method between the bacterial suspension and the filter media. Present work also simulated a prototype of air conditioning in real environment aiming to compare the microbiologic growth in control filter and impregnated with CuNP, simulating an air conditioning system. The composition of both suspensions were a mixture of copper and copper oxide, corroborated with XRD and EDS analysis. The crystallite size was 37 nm to nanoparticles synthesized with PVP, and for those synthesized with starch, the value was 27 nm. Nanoparticles did not have a specific shape and was able to verify that those nanoparticles impregnated to filter media was responsible to the reduction of up to 99,9 % of bacteria. The analysis in real environment was done with the filter with pretreatment done with HCl and impregnated with CuNP synthesized with PVP. It was able to seen that the presence of CuNP in fiber filter showed a biocidal effect when in contact with airborne microorganisms, including fungi. With that, present work showed promisors results to industry, once the indoor air quality it is a public health issue. Several applications can be made with the impregnation of the CuNP to filter medias, including in air filtration of public transports, aviation and even in hospitals applications, as in lab coats, caps and portable air cleaning, aiming to reduce the contamination in those environments.